A 41-Year-Old Man with Two Types of Metachronous Peptic Ulcer Complication due to Zollinger-Ellison Syndrome—Regression of Pancreatic Primary after Chemoembolization of Hepatic Metastases: A Case Report - Seyed Saeid Sarkeshikian; Mohammad Reza Ghadir (Case Reports in Medicine)
Introduction. Gastrinoma should be suspected when the peptic ulcer(s) is postbulbar, multiple, refractory, or recurrent, or ulcer is associated with nephrolithiasis, hypocalcaemia, or erosive esophagitis. The majority of gastrinomas are malignant. Case Presentation. The patient is a 41-year-old Iranian man who has been in good health until 36 months ago when duodenal perforation and two bouts of upper GI bleeding (GIB), each two months apart occurred. He also mentioned mild watery diarrhoea and decreased appetite. Serum gastrin level was elevated. Abdominal CT scan revealed pancreatic mass and three enhancing hepatic masses. CT-guided pancreatic biopsy revealed monotonous cells. Chemoembolization of hepatic metastases was done. New ct images 6 months later showed nearly total regressed hepatic and pancreatic lesions. Conclusion. Beside previously defined situations that take gastrinoma into account as the etiology of PUD, accumulation of PUD complications is highly suggestive of Zollinger-Ellisone syndrome (ZES). Regression of pancreatic primary after chemoembolization of hepatic metastases is unexplainable at the present time.